Subarachnoid injection of ifenprodil and ketamine association improves the anti-hyperalgesic action of ketamine in dogs - Rondon, E. S.; Valadão, C. A.A. [UNESP]; Parada, C. A. (FapUNIFESP (SciELO), 2015)
To test clinically whether a small dose of ifenprodil can enhance the anti-hyperalgesic effect of ketamine in dogs, a prospective randomized cross-over study was done with eight mongrel dogs (weighing 16.9 ± 3.7kg). Animals received two distinct treatments: Ketamine (0.3mg kg-1; KT) and an ifenprodil plus ketamine combination (0.03mg kg-1 and 0.3mg kg-1, respectively; IKT). Dogs were anesthetized with propofol (5mg kg-1 intravenously) and a subarachnoid needle was placed between the 5th and 6th lumbar vertebrae. Five minutes after subarachnoid injection of KT or IKT, an incision including cutaneous and subcutaneous tissues was made on the common pad of one hind limb and was immediately closed with a simple interrupted suture pattern. The dogs were treated again 20 days later, using the contralateral pad and the opposite treatment. Sedation score (SS), lameness score (LS), heart rate (HR), respiratory rate (fR), and mechanical nociceptive threshold using von Frey filaments, were evaluated before anesthesia and at 1, 1.5, 2, 3, 4, 8, 12, and 24 hours after subarachnoid injection. There were no differences in SS, LS, HR or fR between treatments. The intensity of hyperalgesia was higher in KT than in IKT for 24 hours. The anti-hyperalgesic effect of IKT remained without statistical significant difference between 1 and 24 h. Prior subarachnoid administration of ifenprodil enhances the anti-hyperalgesic effect of subarachnoid ketamine in dogs. Ifenprodil can be co-administrated with ketamine to enhance its antihyperalgesic effect and to reduce acute post-incisional hyperalgesia without motor impairment and sedation.
Keywords: Analgesia; Inflammatory pain; NMDA; Pain; Subarachnoid